2021
DOI: 10.3390/genes12081239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Variants of DRD2 and ANKK1 Genes in Combat Athletes

Abstract: The level of physical activity is conditioned by many different factors, including, among others, the personality traits of a person. Important is the fact that personality traits are a moderately heritable factor and on the basis of the analysis of several genes, various lifetime outcomes can be predicted. One of the most important pathways influencing personality traits is connected to the dopaminergic system; hence, we decided to analyze the DRD2 PROM. rs1799732, DRD2 rs1076560, DRD2 Tag1D rs1800498, DRD2 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Despite insignificance, wild-type (G/G) genotype distribution was higher compared to other ones within each group ( Table 1 ). Michałowska-Sawczyn et al (2021) also obtained similar findings, showing that the number of athletes with the G/G genotype was higher, although there were no significant differences observed in their study that included 258 sportsmen and 284 control individuals. Similarly, in another study involving elite rugby players, it was reported that the prevalence of the G/G genotype was higher ( Antrobus et al, 2022a , b ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Despite insignificance, wild-type (G/G) genotype distribution was higher compared to other ones within each group ( Table 1 ). Michałowska-Sawczyn et al (2021) also obtained similar findings, showing that the number of athletes with the G/G genotype was higher, although there were no significant differences observed in their study that included 258 sportsmen and 284 control individuals. Similarly, in another study involving elite rugby players, it was reported that the prevalence of the G/G genotype was higher ( Antrobus et al, 2022a , b ).…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, exercise addiction can negatively impact an individual’s mental health, leading to decreased motivation and focus, which can also hinder athletic performance. Therefore, while exercise addiction and athletic performance can be related, it is essential to maintain a balance between training, and recovery and to seek professional help if addiction symptoms are present ( Murakami et al, 2017 ; Michałowska-Sawczyn et al, 2021 ; Antrobus et al, 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%